2022
DOI: 10.1002/etc.5483
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcome Pathways for Chronic Copper Toxicity to Fish and Amphibians

Abstract: In the present review, we synthesize information on the mechanisms of chronic copper (Cu) toxicity using an adverse outcome pathway framework and identify three primary pathways for chronic Cu toxicity: disruption of sodium homeostasis, effects on bioenergetics, and oxidative stress. Unlike acute Cu toxicity, disruption of sodium homeostasis is not a driving mechanism of chronic toxicity, but compensatory responses in this pathway contribute to effects on organism bioenergetics. Effects on bioenergetics clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 142 publications
1
18
0
Order By: Relevance
“…Overall, results of the current study show that Cu effects on growth and development in X. laevis larvae occurred via a non‐thyroidal AOP consistent with that proposed by Brix et al (2022). This pathway involves multi‐organ cytotoxicity and, at the highest tested Cu concentration, complete growth arrest.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Overall, results of the current study show that Cu effects on growth and development in X. laevis larvae occurred via a non‐thyroidal AOP consistent with that proposed by Brix et al (2022). This pathway involves multi‐organ cytotoxicity and, at the highest tested Cu concentration, complete growth arrest.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, the effects of Cu exposure on advanced development in amphibians have been noted by several investigators (Chai et al, 2017;Fort, Rogers, et al, 2000;Lance et al, 2012;Wang et al, 2016) and is also summarized in Brix et al (2022). Chai et al (2017) found that Cu exposure in B. gargarizan from pre-metamorphic through metamorphic climax decreased metamorphic success, increased HLL, and down-regulated hsp, sod, and phospholipid hydroperoxide glutathione peroxidase (phgpx) implicating the importance of oxidative stress during metamorphosis.…”
mentioning
confidence: 86%
See 3 more Smart Citations